Euro food : sustainable growth driven by entrepreneurial leadership - Lam, Kwok Yan (Nanyang Technopreneurship Center, Nanyang Technological University, 2021)
Mr. Somchai Wachakorn set up European Food Public Co., Ltd (Euro Food) from scratch in 1984. Almost four decades later, through the relentless effort of Mr. Somchai, Euro Food turned out to be one of the leading manufacturers of Confectionery items in Thailand and won consumers’ recognitions. So far, the company has around 2000 employees with a distribution network of more than 50,000 retail outlets, over 10,000 convenient stores throughout Thailand, and operations in 12 countries worldwide. The case unfolded the entrepreneurship journey of Mr. Somchai. It revealed the success factors of the sustainable growth of Euro Food – the entrepreneur’s passion for his goal and perseverance, the two most essential traits of entrepreneurial leadership.